2022
DOI: 10.3390/machines10010056
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Tip Clearance of Axial-Flow Pump on Energy Characteristics under Pump and Turbine Conditions

Abstract: In order to study the influence of tip clearance on the performance and energy dissipation of the axial-flow pump and the axial-flow pump as a turbine, and find the location of high dissipation rate, this study took an axial-flow pump model as its research object and designed four tip radial clearance schemes (0, 0.2, 1 and 2 mm). The unsteady calculation simulation of each tip clearance scheme was carried out based on CFD technology. The calculated results were compared with the experimental results, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Most existing works focus on radial flow pumps as turbines [ 60 ] due to their lower cost and availability. Recent publications concentrate on studying flow features such as rotational speed [ 53 , 55 ], transient behavior [ 54 , 56 ], tip leakage flow [ [61] , [62] , [63] ], entropy production [ 60 , 64 ], and cavitation [ 65 , 66 ] in PATs. Furthermore, there are numerous research works focused on performance improvement [ 40 , 67 ], and a relatively small number of papers examine the economic analysis [ 61 , 62 ] of PATs.…”
Section: Historical Development and The Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Most existing works focus on radial flow pumps as turbines [ 60 ] due to their lower cost and availability. Recent publications concentrate on studying flow features such as rotational speed [ 53 , 55 ], transient behavior [ 54 , 56 ], tip leakage flow [ [61] , [62] , [63] ], entropy production [ 60 , 64 ], and cavitation [ 65 , 66 ] in PATs. Furthermore, there are numerous research works focused on performance improvement [ 40 , 67 ], and a relatively small number of papers examine the economic analysis [ 61 , 62 ] of PATs.…”
Section: Historical Development and The Current Statusmentioning
confidence: 99%
“…Selecting an appropriate pump as a turbine is always challenging because most pump manufacturers do not provide reverse performance data for their pumps [ 15 , 16 , 68 , [63] , [69] , [70] ]. The performance of a PAT is highly dependent on operating conditions, such as the head and flow rate at the site [ 71 ].…”
Section: Pump Selection and Performance Predictionmentioning
confidence: 99%
“…It has been proved by a considerable number of studies that this tip gap has a vital influence on the energy performance in several types of turbomachinery. [9][10][11][12] The pressure difference offers the driving power for the tip clearance leakage flow released from the tip clearance region. As it is known, the complex vortex structures is the main reason causing unstable operation of the centrifugal pump, and it also has a significant effect on the hydraulic losses affecting the pump performance.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is prepared for studying flow characteristics of the AFP during the stall, numerically computing the unsteady flow in the pump under varied working conditions with a focus on analyzing the unstable flow characteristics such as flow separation, typical vortex structure and flow loss in the pump under a variety of working conditions. Li et al 27 studied the effect of tip clearance on each component of the AFP and concluded that the change of tip clearance has a significant impact on the total entropy production of the impeller and guide vane but has little effect on the inlet and outlet pipes. Kan et al 28 studied the influence of the guide vane on the rotational stall of the axial-flow pump and concluded that under the non-design conditions, the large opening of the guide vane causes the impeller to produce backflow, resulting in more energy loss in the pump.…”
Section: Introductionmentioning
confidence: 99%